Experiment on Electricity Consumption Prediction using Long Short-Term Memory Architecture on Residential Electrical Consumer - Md Salleh N.S.; Suliman A.; Jorgensen B.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Benchmarking; Brain; Electric power utilization; Errors; Forecasting; Global warming; Mean square error; Memory architecture; Quality control; Consumption patterns; Electricity demands; Electricity-consumption; Historical dataset; Independent variables; Mean absolute error; Prediction accuracy; Renewable energies; Long short-term memory